Experimental and heat transfer studies of MHP-PV/T by Reynolds number and heat transfer coefficient enhancement - Rui Li; Jinping Li; Junjie Zhu; Xuemin Zhang; Xiao Guo; Vojislav Novakovic (Energy and Built Environment)
The photovoltaic/thermal (PV/T) system, as an energy conversion system to generate electricity and heat, has great application potential in northwest zone of ample solar energy resource in China. The working media inside the micro heat pipe (MHP) of previous studies was acetone. Compared to acetone, R141b has better stability and lower solubility. For working fluid as R141b in the MHP, higher Reynolds Number (Re) theoretically means better heat transfer. During the typical winter season, when the inclination of the PV panel was 45°, the average power conversion efficiency (PCE) and thermal conversion efficiency (TCE) can reach 12.8 and 26.4 %. Furthermore, in order to reduce the simulation time and facilitate the research, the study establishes the fitting equation of MHP-PV/T surface temperature based on solar radiation intensity and environmental temperature with an average error of 7.6 %. Furthermore, a three-dimensional mathematical model of MHP-PV/T system was developed and validated with experimental results, investigating the Re of R141b in the MHPs and calculating the related heat transfer coefficient (h) based on Re. The simulation showed that the Re and h at the condensation section of the MHP were bigger than those at the evaporation section. The Re and h increased with the water temperature decrease of airfoil heat exchanger and solar radiation intensity rise. Lastly, when water temperature of airfoil heat exchanger was unchanged, the impact of solar radiation intensity on h was greater than Re. When the solar radiation intensity remained unchanged and the water temperature decreased, Re was the main reason for affecting the change of h. The research results will give a scientific foundation and technical application for the MHP-PV/T, as well as more efficient solar energy applications in the future.